2015
DOI: 10.3109/19401736.2015.1060439
|View full text |Cite
|
Sign up to set email alerts
|

The complete chloroplast genome sequence of Amentotaxus argotaenia (Taxaceae)

Abstract: The complete chloroplast genome sequence of Amentotaxus argotaenia was determined in this study. The genome is 136 657 bp in length and lacks one inverted repeat region. The overall GC content of the genome is 35.85% (protein-coding genes, 36.90%; tRNA genes, 53.31%; rRNA genes, 52.99%; introns, 36.10%; intergenic spacers, 31.03%). The A. argotaenia chloroplast genome contains 118 unique genes, including 83 protein-coding genes, 31 tRNA genes, and four rRNA genes. Ten protein-coding genes and six tRNA genes ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…In recent decades, several cp genomes of Taxaceae species have been reported, including Amentotaxus formosana (Hsu et al 2014), A. argotaenia (Li et al 2015), T. jackii (Li et al 2017), T. fargesii (Tao et al 2015), and Taxus mairei (Zhang et al 2014). This newly reported chloroplast genome provides a good foundation for the identification and genotyping of Taxaceae species.…”
mentioning
confidence: 83%
“…In recent decades, several cp genomes of Taxaceae species have been reported, including Amentotaxus formosana (Hsu et al 2014), A. argotaenia (Li et al 2015), T. jackii (Li et al 2017), T. fargesii (Tao et al 2015), and Taxus mairei (Zhang et al 2014). This newly reported chloroplast genome provides a good foundation for the identification and genotyping of Taxaceae species.…”
mentioning
confidence: 83%
“…We assembled the chloroplast genomes of A. yunnanensis with A. argotaenia (GenBank: KR780582) (Li J et al. 2016 ) as the reference using MITObim v1.8 (Hahn et al. 2013 ).…”
mentioning
confidence: 99%
“…The Illumina MiSeq sequencing platform (Majorbio Biotech, Shanghai, China) was used to sequence the complete chloroplast genome of A. yunnanensis. We assembled the chloroplast genomes of A. yunnanensis with A. argotaenia (GenBank: KR780582) (Li J et al 2016) as the reference using MITObim v1.8 (Hahn et al 2013). The online tool (DOGMA) was used to annotate the cp genome of A. yunnanensis (Wyman et al 2004).…”
mentioning
confidence: 99%
“…A phylogenetic analysis once suggested that Amentotaxus is a sister genus to Taxus within the Taxaceae family . Similar to Taxus plants, the Amentotaxus species are also evergreen, many-branched shrubs and small trees.…”
mentioning
confidence: 99%